The Leftover Woman: A Novel - Kwok, Jean (New York : William Morrow, an imprint of HarperCollins Publishers, 2023)
"An evocative family drama and a riveting mystery about the ferocious pull of motherhood for two very different women in New York City"--
Keywords: Motherhood -- Fiction; Family secrets -- Fiction; Novels